Ptosis: Clinical overview, etiology and treatment - Solarz, Adam; Szabelski, Szymon; Skibicka, Katarzyna; Graczyk, Estera; Cwalina, Oliwia; Kryślak, Joanna; Sokołowski, Maciej; Oskroba, Karolina; Turcza, Jakub Filip; Woś, Małgorzata (Quality in Sport, 2025)
Ptosis is a condition characterized by a low setting of the upper eyelid caused by congenital or acquired dysfunction of the levator muscle. The problem can occur unilaterally or bilaterally, in any age group, and affects over 1 million patients in Poland, with varying degrees of severity. Drooping of the upper eyelid leads to secondary restriction of the visual field, deterioration of vision quality, as well as a subjective decrease in visual acuity. Additionally, it is an aesthetic defect, which consequently negatively impacts the patient's quality of life, self-esteem, and social perception. This article presents key information about ptosis, including clinical implications, etiology, and classification, as well as diagnostic algorithms and methods, and modern surgical treatment approaches.